2021
DOI: 10.1016/j.apsb.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound FLZ alleviates rotenone-induced PD mouse model by suppressing TLR4/MyD88/NF-κB pathway through microbiota–gut–brain axis

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease, but none of the current treatments for PD can halt the progress of the disease due to the limited understanding of the pathogenesis. In PD development, the communication between the brain and the gastrointestinal system influenced by gut microbiota is known as microbiota–gut–brain axis. However, the explicit mechanisms of microbiota dysbiosis in PD development have not been well elucidated yet. FLZ, a novel squamosamide derivative, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 75 publications
(114 reference statements)
2
33
0
Order By: Relevance
“…The expression of IDO and TDO, the rate-limiting enzymes in the Trp/Kyn metabolism pathway, was observed in various cancer, including hepatic carcinoma [ 6 , 7 , 15 , 16 ]. To investigate the role of Trp metabolic enzymes, we examined the expression of IDO1 and TDO2 in tumor tissues from liver cancer patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of IDO and TDO, the rate-limiting enzymes in the Trp/Kyn metabolism pathway, was observed in various cancer, including hepatic carcinoma [ 6 , 7 , 15 , 16 ]. To investigate the role of Trp metabolic enzymes, we examined the expression of IDO1 and TDO2 in tumor tissues from liver cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, upregulation of Trp metabolism induced by IDO/TDO enzymes represents one of the most important pathways for tumor occurrence and development [ 5 ]. IDO1 and TDO2 enzymes catalyze Trp oxidation to Kyn, which are frequently observed in tumor tissues and tightly correlated with the poor prognosis in patients [ 6 , 7 ]. Kyn synthesis has been demonstrated to promote tumorigenicity and growth by activating pro-survival signaling pathways, including PI3K/AKT and Wnt/β-catenin signals [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, adult male rats and mice have been widely used in the study of PD [38][39][40][41]. In this study, adult male Sprague-Dawley rats (used for detecting the expression of AAV8-MANF and RNA-seq) and male C57/BL6 mice (used for exploring the protection of AAV8…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…In line with this, studies have found that the loss of function or inhibition of TLR4 suppresses AD progression in the mouse model [35,36]. Moreover, previous studies showed that inhibiting the TLR4 pathway alleviated motor impairment and dopaminergic neuron death in the Parkinson's disease mouse model [37]. And Kwilasz et al showed that TLR4 antagonists prevented the production of proinflammatory factors and motor dysfunction in the experimental autoimmune encephalomyelitis mouse model [38].…”
Section: Discussionmentioning
confidence: 78%